Monocyte Subset Recruitment Marker Profile Is Inversely Associated With Blood ApoA1 Levels - Patel, Vyoma K.; Williams, Helen; Li, Stephen C. H.; Fletcher, John P.; Medbury, Heather J. (Frontiers in Immunology, 2021)
Dyslipidaemia promotes development of the inflammatory plaques characteristic of cardiovascular disease (CVD). We previously found that the inflammatory state of monocytes is related to individuals’ lipid levels. This altered state would have greater impact on plaque development if accompanied by an increased ability to extravasate. Recruitment marker expression on the three main monocyte subsets relative to lipid levels was examined here. We found that the well-recognised inter-subset differences in expression of adhesion molecules and chemokine receptors were largely overshadowed by considerable inter-participant differences. All monocytes of some individuals have a greater potential to migrate than those of other individuals due to their elevated levels of recruitment makers. This, plus the considerable correlations between the expression of most recruitment markers would enable their monocytes to migrate using a wider repertoire of recruitment markers than currently appreciated. The inter-participant differences were partly explained by lipid levels; most notably, an inverse relationship with ApoA1- the main protein associated with HDL. The increased migratory ability of these inflammatory monocytes in dyslipidemia would promote plaque progression, and furthermore, impact the immune response to other conditions, such as infection. With dyslipidemia being extremely common this immunopathology is likely prevalent, largely undetected, in the general population.